2020
DOI: 10.17263/jlls.712635
|View full text |Cite
|
Sign up to set email alerts
|

Transferring L1 reading attitudes to EFL reading habits

Abstract: The aim of the current study is to find out the possibility of transfer of affective domains of reading specifically reading habits and attitudes from L1 to EFL and the role of learners' proficiency level on these reading habits and attitudes. The study was designed as a descriptive research. The participants were 273 university-level students who enrolled in English classes in a state university in Turkey. 136 of them were at beginner level (A1) and 137 of them were at elementary (A2) level according to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this respect, in Sparks et al's (2012) study, L1 reading amount was the significant predictor of L2 proficiency and several L2 skills. Similarly, Artieda (2017) and Uslu (2020) found that strong L1 reading habits significantly contribute to learners' L2 achievement. Regular reading motivation and strong reading habits in L1 can significantly affect L2 reading habits and motivation (Iftanti,2015).…”
Section: Reading Habits In L1 and L2mentioning
confidence: 91%
“…In this respect, in Sparks et al's (2012) study, L1 reading amount was the significant predictor of L2 proficiency and several L2 skills. Similarly, Artieda (2017) and Uslu (2020) found that strong L1 reading habits significantly contribute to learners' L2 achievement. Regular reading motivation and strong reading habits in L1 can significantly affect L2 reading habits and motivation (Iftanti,2015).…”
Section: Reading Habits In L1 and L2mentioning
confidence: 91%
“…One of the elements influencing attitudes toward reading is EFL reading ability (Uslu, 2020). Active thought is required for reading comprehension (Mikulecky & Jeffries, 2007).…”
Section: Reading Comprehensionmentioning
confidence: 99%
“…Reading is considered a necessary skill that can help the students achieve their academic achievement. Students with advanced reading skills will make greater progress in all other fields of learning (Uslu, 2020). Reading activity is often related to the term reading interest.…”
Section: Introductionmentioning
confidence: 99%